2014
DOI: 10.1016/j.jvs.2013.10.088
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the association between markers of hemostasis and abdominal aortic aneurysm presence and size

Abstract: This study suggests that the presence of AAAs is associated with increased fibrin turnover, fibrinolysis, and thrombin generation, as shown by increased levels of fibrinogen, D-dimer, and thrombin-antithrombin III complex. This is clinically relevant because markers of hemostasis are independent risk factors for cardiovascular events, highlighting the necessity of addressing all modifiable cardiovascular risk factors in patients with AAAs. Furthermore, the finding that plasma D-dimer concentration appears to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 43 publications
5
56
0
6
Order By: Relevance
“…Importantly, platelets and platelet-specific secretions (soluble P-selectin, soluble CD40L, soluble glycoprotein V, and platelet-derived microparticles) are present in plasma of AAA patients and are specifically released from the luminal thrombus of an aneurysm (25). Despite these results, several meta-analyses and retrospective clinical trials reported no significant benefit of platelet inhibitors on aneurysm growth and incidence of rupture (32-34). …”
Section: Introductionmentioning
confidence: 98%
“…Importantly, platelets and platelet-specific secretions (soluble P-selectin, soluble CD40L, soluble glycoprotein V, and platelet-derived microparticles) are present in plasma of AAA patients and are specifically released from the luminal thrombus of an aneurysm (25). Despite these results, several meta-analyses and retrospective clinical trials reported no significant benefit of platelet inhibitors on aneurysm growth and incidence of rupture (32-34). …”
Section: Introductionmentioning
confidence: 98%
“…While contemporary imaging can readily determine the dimensions of AAAs, one of the hopes of biomarkers is their ability to discriminate propensity to rupture. Recently, two large meta-analysis studies assessed a wide array of molecular markers for application as AAA biomarkers [17,18]. Sidloff et al [17] demonstrated significant increase plasma concentrations of fibrinogen, D-dimer, and thrombin-antithrombin III complex in people with AAA; and also a significant correlation between aortic diameter and D-dimer In addition to these hemostasis markers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two large meta-analysis studies assessed a wide array of molecular markers for application as AAA biomarkers [17,18]. Sidloff et al [17] demonstrated significant increase plasma concentrations of fibrinogen, D-dimer, and thrombin-antithrombin III complex in people with AAA; and also a significant correlation between aortic diameter and D-dimer In addition to these hemostasis markers. Stather et al [18*] demonstrated a significant difference in a number of biomakers in patients with AAAs including: matrix metalloproteinase (MMP) 9, tissue inhibitor of matrix metalloproteinase 1, interleukin (IL) 6, Creactive protein (CRP), α1-antitrypsin, apolipoprotein A and high-density lipoprotein.…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative assessment of changes in tissue factor and its inhibitor in patients with abdominal aortic aneurysm treated using classical and intravascular methods the bloodstream [7][8][9] and elevated TF in plasma is the evidence of the state of hyper coagulation. Previously Hobbs and co-workers showed the elevated level of TF in patients with ruptured AAA when compared to asymptomatic patients without concurrent differences in TFPI levels [10].…”
Section: Resultsmentioning
confidence: 99%